Quality of Life for a Sample of Adults in Jordan in the Presence of the Corona Pandemic - Altareefi, Maysaa Ahmad; Alnaimat, Mahmoud Haroun (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the level of quality of life for a sample of adults in Jordan in the presence of the corona pandemic, where the two researchers used the descriptive approach, both analytical and correlational, the study sample consisted of (285) adults who were selected in a simple random way. The results showed that the quality of life of the sample was average, and indicated that there are apparent differences between the arithmetic averages in the quality of life of the sample according to gender, age and marital status, and the absence of statistically significant differences in degree The total quality of life of the sample in light of the Corona pandemic and its dimensions attributable to gender, the existence of differences in the dimension of (social life) and in favor of females, the existence of differences in the total degree of the level of quality of life of the sample in light of the Corona pandemic and its dimensions attributable to the social situation in favor of singles, and the existence of differences in the total degree of the level of The quality of life is attributed to age in favor of those of their ages (18-30 years), that is, young people feel more of a quality of life, and the researchers recommended several results, including the status of The necessary support mechanisms to mitigate the negative effects of the Corona crisis on health and well-being, especially for the elderly.
Keywords: Quality of Life; Corona Pandemic; Adults